CD4+ T Cell Fate in Glomerulonephritis: A Tale of Th1, Th17, and Novel Treg Subtypes - Christan F. Krebs; Oliver M. Steinmetz (Hindawi Limited, 2016)
Multiple studies have identified CD4+ T cells as central players of glomerulonephritis (GN). Cells of the Th1 and Th17 responses cause renal tissue damage, while Tregs mediate protection. Recently, a high degree of plasticity among these T cell lineages was proposed. During inflammation, Th17 cells were shown to have the potential of transdifferentiation into Th1, Th2, or alternatively anti-inflammatory Tr1 cells. Currently available data from studies in GN, however, do not indicate relevant Th17 to Th1 or Th2 conversion, leaving the Th17 cell fate enigmatic. Tregs, on the other hand, were speculated to transdifferentiate into Th17 cells. Again, data from GN do not support this concept. Rather, it seems that previously unrecognized subspecialized effector Treg lineages exist. These include Th1 specific Treg1 as well as Th17 directed Treg17 cells. Furthermore, a bifunctional Treg subpopulation was recently identified in GN, which secrets IL-17 and coexpresses Foxp3 together with the Th17 characteristic transcription factor RORγt. Similarities between these different and highly specialized effector Treg subpopulations with the corresponding T helper effector cell lineages might have resulted in previous misinterpretation as Treg transdifferentiation. In summary, Th17 cells have a relatively stable phenotype during GN, while, in the case of Tregs, currently available data suggest lineage heterogeneity rather than plasticity.